Mental Health Status and its Relationship with Accident and Unsafe Behavior in a Printing and Press Industry, 2014 - Mohammad Khandan; Alireza Koohpaei (Iranian Journal of Health, Safety and Environment, 2016)
Physical and psychological health of workers is critical factors in the performance of their works. Also, the number of fatal occupational accidents is high in our country. Based on these facts assessment and control of accidental determinants as well as their relationship with behavior and mental health of workers is vital. This study aimed to survey the relationship between general health, occupational accident, behavioral safety and demographic variables in a printing and publication industry located at a central province of Iran in 2014. In this cross-sectional study, all operational employees (98 persons) were included. Demographic questionnaires, Goldberg general health-28, safety behavior checklist and self-reported accidents were tools used to gather data. Statistical analysis such as independent T-test, ANOVA and Pearson correlation were used and evaluation of data was done using SPSS V20. All workers were men of mean age 41.79±6.77. Studied personnel who had experienced occupational accidents were in the case range of 0-5. Furthermore, 80.75% of the total observed behaviors (800) were safe. Mean score of GHQ test was equal to 50.38±10.39 which was over 23 as the cut-off point. There was no significant relationship between mental health with safe behaviors (p>0.05). In summary workers' mental health status was unacceptable. Although, conditions of work which was based on the occupational accident and safety behavior have not shown any situation of caution, using ABC model (Activators-Behaviors-Consequences) can help promote personnel behaviors and anticipate accident control.